Herpes zoster in a healthy child-a rarity - Sharma, Anuj; Rattan, Renu (International Journal of Research in Medical Sciences, 2017)
Herpes zoster, caused by Varicella-zoster virus is generally considered to be a disease of the elderly. Recently, a number of studies have shown in the increased incidences in children. Herein, a case of Herpes zoster in an otherwise healthy child of 9 years of age is being reported, who did not have any evidence of immunosupression.